2014
DOI: 10.1111/den.12265
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of low‐volume (2 L) versus single‐ (4 L) versus split‐dose (2 L + 2 L) polyethylene glycol bowel preparation for colonoscopy: Randomized clinical trial

Abstract: Preparation with 2 L caused less abdominal discomfort and fewer sleep disorders. The split dose had a better quality of preparation in the right colon. Both preparations were clearly better than the 4-L preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
0
22
1
4
Order By: Relevance
“…Thus, adequate bowel preparation for colonoscopy remains a practical concern in the elderly population. Previous studies have consistently reported that split-dose PEG is superior to single-dose PEG with respect to the coloncleansing quality and tolerability [4,17,21,[24][25][26][27][28] . A recent meta-analysis evaluating 7,719 subjects in 29 studies also showed the superiority of a split-dose regimen over a non-split-dose regimen, regardless of purgative type or dose [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, adequate bowel preparation for colonoscopy remains a practical concern in the elderly population. Previous studies have consistently reported that split-dose PEG is superior to single-dose PEG with respect to the coloncleansing quality and tolerability [4,17,21,[24][25][26][27][28] . A recent meta-analysis evaluating 7,719 subjects in 29 studies also showed the superiority of a split-dose regimen over a non-split-dose regimen, regardless of purgative type or dose [5] .…”
Section: Discussionmentioning
confidence: 99%
“…A sample-size calculation was carried out based on previously published data, indicating a good to excellent preparation in 90% of patients receiving split-dose PEG preparation and in 70% of patients receiving single-dose PEG (4 L) preparation the day before colonoscopy [21] . To achieve an absolute difference of 20% in the frequency of good to excellent quality of cleansing in the colon (score ≥ 2) with a statistical type I error of 5% and a statistical power of 80%, a total of 186 participants (62 participants per group) was calculated to be required.…”
Section: Outcome Measurements and Statistical Analysismentioning
confidence: 99%
“…In recent studies [21][22][23], low-volume bowel preparations have shown improved tolerability and successful bowel cleansing compared with large-volume (4-L) PEG preparations. However, few reports have compared SPMC and PEG-Asc, which are representative low-volume bowel preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recently published study using 2-liter PEG without any adjunctive laxative in the morning of the procedure date, together with keeping 2-7h interval between the last dose of cleansing agent and colonoscopy resulted in a similar bowel preparation quality compared to standard split-dose 4-liter PEG regimen (Tellez-Avila FI et al, 2014). These can be concluded that time interval between last dose of cleansing agent and procedure is more important than volume of PEG ingested.…”
Section: Discussionmentioning
confidence: 95%